Global burden of gallbladder and biliary diseases: A systematic analysis for the Global Burden of Disease Study 2019. Issue 7 (24th April 2022) - Li, Jiamei; Jin, Xuting; Ren, Jiajia; Li, Ruohan; Du, Linyun; Gao, Ya; Zhang, Jingjing; Liu, Xiu; Wang, Xiaochuang; Wang, Gang
Abstract: Background and Aim: Gallbladder and biliary diseases (GBDs) are one of the most prevalent medical issues in the digestive system. This study was designed to describe the characteristics of prevalence, death, and disability‐adjusted life years (DALYs) of GBDs during 1990–2019 using data from the Global Burden of Diseases, Injuries, and Risk Factors Study 2019. Methods: Prevalence, death, and DALYs for GBDs in different locations, years, sex, and age groups were estimated using DisMod‐MR 2.1 and a generic Cause of Death Ensemble Modeling approach. Countries and territories were categorized according to socio‐demographic index (SDI) quintiles. Results: The prevalence cases (127 345 732 to 193 493 378), death cases (82 430 to 124 941), and DALYs (4 604 821 to 6 352 738) of GBDs increased from 1990 to 2019. However, the age‐standardized rates of indicators decreased over the 30‐year period (prevalence, 2851.84 to 2350.78 per 100 000 population; death, 2.40 to 1.65 per 100 000 population; DALYs, 106.76 to 78.25 per 100 000 population). In 2019, the high and middle–high SDI regions had higher age‐standardized prevalence rates, the low SDI region had the highest age‐standardized death rate, and the middle SDI region had the highest DALYs and age‐standardized DALYs rate of GBDs. Being female, older age, and high body mass index were important risk factors for the burden of GBDs. Conclusions: Globally, there were improvements in overall health with regard to GBDs over the 30 years. However, the prevention of GBDs should be promoted in middle, middle–high, and high SDI regions, while more medical resources should be provided to improve treatment levels in low SDI region.